The plot to betray America : how team Trump embraced our enemies, compromised our security, and how we can fix it - Nance, Malcolm W. (New York : Hachette Books, 2019)
"When former FBI Director Robert Mueller III was assigned to the Special Counsel investigation looking into the possibility of Russian interference in the 2016 US election, many Americans felt relieved. But when the report was delivered in April 2019, it was clear that the case was far from closed--and pinning Trump down on conspiracy charges was going to be a lot more difficult than it had first seemed. In [this book], Malcolm Nance, ... bestselling author and renowned intelligence expert, reveals exactly how Trump and his inner circle conspired, coordinated, communicated, and eventually strategized to commit the greatest act of treachery in the history of the United States: compromising the presidential oath of office in exchange for power and personal enrichment. Seduced by the promises of riches dangled in front of them by Vladimir Putin, the Trump administration eagerly decided to reap the rewards of the plan to put a Kremlin-friendly crony in the Oval Office. And instead of interfering, the Republican Party's faithful William Barr, Paul Manafort, Michael Cohen, Steve Bannon, Rudy Giuliani, Mitch McConnell, Roger Stone, George Papadopoulos, and Jeff Sessions among others did everything they could to facilitate Trump's damage to national security to fill his own pockets. Through in-depth research and interviews with intelligence experts and insiders, Nance charts Trump's deep financial ties to Russia through his family's investments, including those of Donald Trump Jr., Ivanka Trump, and Jared Kushner, and the corrupt behavior of his other double-crossing pro-Moscow associates. Only by untangling the spider web of personal and financial relationships linking the White House to the Kremlin can we start to free ourselves from the constricting clutches of our foreign adversaries and work to rebuild our fractured nation. In this geopolitical page-turner, The Plot to Betray America ultimately sketches the tracks and blueprint of the Trump administration's conspiracy against our country-and how we can still fight to defend democracy, protect our national security, and save the Constitution."--Dust jacket.
Section I: Organizing to steal an election. Betraying the oath . . . in plain sight ; The super villain with a leash ; Trump: the dog to be walked ; Swimming in rubles ; Team Trump ; The dynastic crime family ; The five dangles ; Team Dirty Tricks -- Section II: The mischief begins. The worst presidency in history ; Masters of fake news ; The good guys ; All the (Russian) president's men ; The Trump doctrine: buying this American, buys America ; Hydra 2.0--destroying America's security from within -- Section III: Obstruction of justice. The asteroid of awfulness ; "The end of my presidency . . ." ; Fixing a fractured democracy -- Epilogue: Benedict Arnold vindicated.
Includes bibliographical references and index.
Keywords: Trump, Donald, -- 1946-; Putin, Vladimir Vladimirovich, -- 1952-; Putin, Vladimir Vladimirovich, -- 1952-; Trump, Donald, -- 1946-; 2017-2021; Political corruption -- United States; POLITICAL SCIENCE / Intelligence & Espionage; POLITICAL SCIENCE / Political Ideologies / Democracy; POLITICAL SCIENCE / Political Ideologies / Fascism & Totalitarianism; Political corruption; Politics and government; United States -- Politics and government -- 2017-2021; United States